Bibliometric study on artistic swimming - Rincón, Ane Begoñe; Trinidad, Alfonso; López-Valenciano, Alejandro (Frontiers in Sports and Active Living, 2023)
Introduction The objective of this paper is to study the research trends in the sport modality of artistic swimming and to analyse the scientific production regarding this sport. Methods Two hundred and twenty articles related to the theme were selected after a search in the PubMed, SPORTDiscus and Web of Science databases and some additional records, using the theme “synchronised swimming OR artistic swimming” up to December 2022. The variables scrutinized were the following: (1) title, (2) discipline, (3) type, (4) sample size and (5) sporting level. Results The results indicate that (1) 53.6% of the artistic swimming articles were case studies, (2) 23.2% talked about physiology, (3) 32.7% had a sample of 11–50 participants, and (4) 30.9% of the sample was elite/international swimmers. Discussion Over the years there has been a considerable increase in studies on artistic swimming; the topics of greatest interest in artistic swimming have been physiology, sports performance and injuries. Even so, it seems that for the moment artistic swimming has little impact, probably due to its status as a minority sport and it having limited social and economic impact.